GWAS analysis reveals distinct pathogenicity profiles of Australian Parastagonospora nodorum isolates and identification of marker-trait-associations to septoria nodorum blotch - Phan, Huyen; Furuki, Eiko; Hunziker, Lukas; Clarke, Kasia; Tan, Kar-Chun (Nature Publishing Group, 2021)
The fungus Parastagonospora nodorum is the causal agent of septoria nodorum leaf blotch (SNB) and glume blotch which are common in many wheat growing regions in the world. The disease is complex and could be explained by multiple interactions between necrotrophic effectors secreted by the pathogen and matching susceptibility genes in wheat. An Australian P. nodorum population was clustered into five groups with contrasting properties. This study was set to identify their pathogenicity profiles using a diverse wheat panel of 134 accessions which are insensitive to SnToxA and SnTox1 in both in vitro and in vivo conditions. SNB seedling resistance/susceptibility to five representative isolates from the five clusters, responses to crude culture-filtrates (CFs) of three isolates and sensitivity to SnTox3 semi-purified effector together with 11,455 SNP markers have been used for linkage disequilibrium (LD) and association analyses. While quantitative trait loci (QTL) on 1D, 2A, 2B, 4B, 5B, 6A, 6B, 7A, 7D chromosomes were consistently detected across isolates and conditions, distinct patterns and isolate specific QTL were also observed among these isolates. In this study, SnTox3–Snn3-B1 interaction for the first time in Australia and SnTox3–Snn3-D1 interaction for the first time in bread wheat were found active using wild-type isolates. These findings could be due to new SnTox3 haplotype/isoform and exotic CIMMYT/ICARDA and Vavilov germplasm used, respectively. This study could provide useful information for dissecting novel and different SNB disease components, helping to prioritise research targets and contributing valuable information on genetic loci/markers for marker-assisted selection in SNB resistance wheat breeding programme.